(untitled) (Aporte Santiaguino, 2025)
This study evaluated the chemical (degradation level) and physical-mechanical (damage and tear resistance) properties of Mater-Bi bioplastic mulch and LDPE (low-density polyethylene) mulch as applied in experimental plots of canary bean cultivation. Both materials were tested under high-altitude conditions (2800 masl) at the Tuyu Ruri Ecological Experimental Center, Callejón de Huaylas interandean valley, Peru. A completely randomized experimental design was used, with two treatments and two repetitions (4 experimental units), the evaluation spanned 20 weeks, rates on a scale from 9 to 1. Mater-Bi demonstrated rapid degradation, with a rating of 7 by the fifth week and 4 by the twentieth week, with lesions and holes predominantly in areas exposed to direct sunlight and wind rated 4, and tear strength rated 3, reflecting its progressive fragility as degradation progressed. In contrast, LDPE remained intact throughout the cultivation period, with minimal physical damage and high resistance to degradability and tearing. These findings highlight the potential benefits and limitations of biodegradable plastics for sustainable agriculture at high altitudes.